2022
DOI: 10.1186/s12883-022-02628-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–Phenotype correlations of SCARB2 associated clinical presentation: a case report and in-depth literature review

Abstract: Background Biallelic pathogenic variants in the SCARB2 gene have been associated with action myoclonus-renal failure (AMRF) syndrome. Even though SCARB2 associated phenotype has been reported to include typical neurological characteristics, depending on the localization and the feature of the pathogenic variants, clinical course and the presentations have been shown to differ. Case presentation Whole exome sequencing (WES) analysis revealed a homoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…GALCGalactosylceramidase, a lysosomal protein that hydrolyzes the galactose ester bonds of galactosylceramide; associated with Krabbe disease Shang et al[116] SCARB2 Scavenger receptor class B member 2, a type III glycoprotein found mostly in limiting membranes of lysosomes and endosomes; it may participate in membrane transportation Quraishi et al[117] Atasu et al[118] Yari et al[119] …”
mentioning
confidence: 99%
“…GALCGalactosylceramidase, a lysosomal protein that hydrolyzes the galactose ester bonds of galactosylceramide; associated with Krabbe disease Shang et al[116] SCARB2 Scavenger receptor class B member 2, a type III glycoprotein found mostly in limiting membranes of lysosomes and endosomes; it may participate in membrane transportation Quraishi et al[117] Atasu et al[118] Yari et al[119] …”
mentioning
confidence: 99%